Assessing children's competence in computer interactions: preliminary reliability and validity of the Test of Mouse Proficiency. - Lane A; Ziviani J (OTJR: Occupation, Participation & Health)
The Test of Mouse Proficiency (TOMP) was developed to assist occupational therapists and education professionals assess computer mouse competency skills in children from preschool to upper primary (elementary) school age. The preliminary reliability and validity of TOMP are reported in this paper. Methods used to examine the internal consistency, test-retest reliability, and criterion- and construct-related validity of the test are elaborated. In the continuing process of test refinement, these preliminary studies support to varying degrees the reliability and validity of TOMP. Recommendations for further validation of the assessment are discussed along with indications for potential clinical application.